Drugfever: Case report - Siti Nurdjanah, Siti Nurdjanah (Universitas Gadjah Mada, 1991)
Fever is a feature of a variety of infectious and non-infectious diseases. Recognition of drug fever in hospitalized patients is critical. If the condition is not appreciated, the patient may be subjected to prolonged hospitalization and a variety of unnecessary antibiotics, laboratory, and radiologic studies.Fever is considered to be drug-induced, -an incompletely understood allergic hypersensitivity reaction to medication-, if other causes can be eliminated, if the temperature elevation is temporally associated with the administration ofsensitizing medication, and if the fever disappears within 72 hours after discontinuation of the medication. Any drug has the capacity to induce fever as an adverse reaction.This article reported three cases of drug fever. Patients appeared